Digitalisasi Pendidikan Agama Islam: Peran Software dalam Proses Pembelajaran - Nur, Zulfikah; Yaumi, Muhammad; Arsyad, Azhar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the benefits and challenges of software implementation. This study uses a literature study method to explore the role of software in the digitization of Islamic education. The sources were selected based on their relevance to key themes, including the integration of technology in Islamic education, the use of digital tools in the pedagogical process, and the challenges and opportunities associated with educational software. Data collection follows a structured process, which involves searching for keywords in databases such as Google Scholar with terms such as "digital Islamic education", "educational software in Islamic studies", and "technology in religious learning". This analysis focuses on categorizing findings into thematic areas, including teaching methods, learner engagement, and teacher support, to provide a comprehensive understanding of the subjects. The results of the analysis show that the integration of software in Islamic Religious Education learning provides many benefits, such as increasing interactivity and accessibility of learning. However, its implementation requires adequate infrastructure support and training. The benefits of Technology Integration are interactivity, helping to create an interesting, dynamic learning environment, and supporting active student participation. Accessibility allows students and teachers to access a wider range of learning resources, anytime and anywhere